2021
DOI: 10.1371/journal.pone.0257351
|View full text |Cite
|
Sign up to set email alerts
|

Development of in-house, indirect ELISAs for the detection of SARS-CoV-2 spike protein-associated serology in COVID-19 patients in Panama

Abstract: COVID-19 is the name of the acute respiratory disease caused by the new coronavirus SARS-CoV-2, a close relative of those that caused the severe outbreaks of SARS and MERS several years ago. Since first appearance on December of 2019, the COVID-19 pandemic has cause extremely high levels of mortality, morbidity, global economic breakdown, and the consequent human suffering. The main diagnostic test for the confirmation of symptomatic individuals is the detection of viral RNA by reverse transcriptase–quantitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…At the international level, similar studies describing COVID-19 immunoassays have been reported from several research groups [ 29 , 30 , 31 , 32 , 33 , 34 ]. Most of these immunoassays were based on SARS-CoV-2 full-length S, NP, or fragments of S (e.g., receptor binding domain).…”
Section: Development Of Serological Assays For Covid-19supporting
confidence: 54%
See 1 more Smart Citation
“…At the international level, similar studies describing COVID-19 immunoassays have been reported from several research groups [ 29 , 30 , 31 , 32 , 33 , 34 ]. Most of these immunoassays were based on SARS-CoV-2 full-length S, NP, or fragments of S (e.g., receptor binding domain).…”
Section: Development Of Serological Assays For Covid-19supporting
confidence: 54%
“…In some cases, assays were optimized not only for detection of IgM and IgG, but also for IgA [ 33 ]. Validation of results was also evaluated against RT-PCR, the MN assay, and commercially available kits [ 29 , 30 , 31 , 32 , 33 , 34 ]. Herein, we review several in-house immunoassays developed in Saudi Arabia.…”
Section: Development Of Serological Assays For Covid-19mentioning
confidence: 99%
“…As E. coli RBD did not provide good results in the IgG-based ELISA, although it bound to the ACE2 receptor, it was not further considered for testing [24]. Thus, RBD was expressed in HEK cells, as previous reports indicated also a good sensitivity in ELISA [16,[25][26][27]. When the monomeric and dimeric versions of RBD expressed in HEK cells in-house and two commercial RBDs were coated in ELISA, the obtained OD 450 -values were identical within the error range (Figure S7).…”
Section: Elisamentioning
confidence: 99%
“…All pre-pandemic serum samples remained unreactive. Some samples in the COVID-19 group showed low OD readouts similar to healthy samples, suggesting a lack of or a weak seroconversion 64,68,69 . Next steps may involve testing cross reactivity with patient samples of other coronaviruses.…”
Section: Discussionmentioning
confidence: 98%